2002
DOI: 10.1111/j.1348-0421.2002.tb02669.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of C3a and C5a Octapeptides by Carboxypeptidase R and Carboxypeptidase N

Abstract: Pro-carboxypeptidase R (proCPR), also known as thrombin-activatable fibrinolysis inhibitor (TAFI), precursor of carboxypeptidase U and plasma carboxypeptidase B is present in plasma and following activation by thrombin/thrombomodulin and/or plasmin can remove arginine from the carboxyterminal of C3a and C5a. We have shown that this enzyme can remove terminal arginine from the C5a octapeptide much more efficiently than the classical anaphylatoxin inactivator, carboxypeptidase N (CPN). Since we have previously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
167
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(174 citation statements)
references
References 18 publications
(16 reference statements)
2
167
0
1
Order By: Relevance
“…To test this, we studied the kinetics of TAFIa hydrolysis of BK and peptides based on the thrombincleaved OPN SVVYGLR motif and the C-terminal residues of C3a, C5a and compared these to peptides based on exposed C-terminal arginine or lysine sites on plasmin-degraded fibrin clots (27 It is interesting that plasma CPN, generally thought to be the physiological inactivator of the kinins and anaphylatoxins, hydrolyzed the fibrin peptides quite efficiently, suggesting a possible role of CPN in the maintenance of fibrin clot stability. CPN is more efficient in hydrolyzing C3a than C5a, while TAFIa shows the opposite preference, consistent with previous findings (13). On the other hand, in addition to C5a, TAFIa is also much more efficient than CPN in cleaving BK and OPN 160 -168 .…”
Section: Fig 1 Effect Of Tafia Treatment On Thrombin-cleaved Gst-opsupporting
confidence: 81%
See 3 more Smart Citations
“…To test this, we studied the kinetics of TAFIa hydrolysis of BK and peptides based on the thrombincleaved OPN SVVYGLR motif and the C-terminal residues of C3a, C5a and compared these to peptides based on exposed C-terminal arginine or lysine sites on plasmin-degraded fibrin clots (27 It is interesting that plasma CPN, generally thought to be the physiological inactivator of the kinins and anaphylatoxins, hydrolyzed the fibrin peptides quite efficiently, suggesting a possible role of CPN in the maintenance of fibrin clot stability. CPN is more efficient in hydrolyzing C3a than C5a, while TAFIa shows the opposite preference, consistent with previous findings (13). On the other hand, in addition to C5a, TAFIa is also much more efficient than CPN in cleaving BK and OPN 160 -168 .…”
Section: Fig 1 Effect Of Tafia Treatment On Thrombin-cleaved Gst-opsupporting
confidence: 81%
“…DISCUSSION A major premise of this study is that TAFIa has broad substrate specificity, and by cleaving C-terminal arginine or lysine from a number of biologically active peptides, it functions as an anti-inflammatory molecule. Initial studies by Campbell and co-workers (4,12,13) showed that TAFIa could have a role as a regulator of inflammation by inactivation of kinins and anaphylatoxins. To test this, we studied the kinetics of TAFIa hydrolysis of BK and peptides based on the thrombincleaved OPN SVVYGLR motif and the C-terminal residues of C3a, C5a and compared these to peptides based on exposed C-terminal arginine or lysine sites on plasmin-degraded fibrin clots (27 It is interesting that plasma CPN, generally thought to be the physiological inactivator of the kinins and anaphylatoxins, hydrolyzed the fibrin peptides quite efficiently, suggesting a possible role of CPN in the maintenance of fibrin clot stability.…”
Section: Fig 1 Effect Of Tafia Treatment On Thrombin-cleaved Gst-opmentioning
confidence: 99%
See 2 more Smart Citations
“…CPB inactivates bradykinin, C3a and C5a. 18,19 We have demonstrated that CPB is much more efficient than CPN, the constitutively active plasma anaphylatoxin inhibitor, in cleaving these inflammatory peptides. CPB abrogated C5a-induced neutrophil activation in vitro, and, using an engineered anticoagulant thrombin, E229K, which activates plasma proCPB in mice, we showed that E229K thrombin blocked bradykinin-induced hypotension in wild-type (WT), but not in proCPB-deficient (proCPB Ϫ/Ϫ ) mice in vivo.…”
Section: Introductionmentioning
confidence: 99%